Effect of body surface area and gender on wall thickness thresholds in hypertrophic cardiomyopathy - Huurman, R. (Neth Heart J, 2019)
BACKGROUND: Family screening for hypertrophic cardiomyopathy (HCM) is based on genetic testing and clinical evaluation (maximal left ventricular wall thickness (MWT) ≥15 mm, or ≥13 mm in first-degree relatives of HCM patients). The aim of this study was to assess the effect of gender and body size on diagnosis of HCM and prediction of clinical outcome. METHODS: This study includes 199 genotype-positive subjects (age 44 ± 15 years, 50% men) referred for cardiac screening. Gender-specific reference values for MWT indexed by body surface area (BSA), height and weight were derived from 147 healthy controls. Predictive accuracy of each method for HCM-related events was assessed by comparing areas under the receiver operating characteristic curves (AUC). RESULTS: Men had a higher absolute, but similar BSA- and weight-indexed MWT compared with women (14.0 ± 3.9 mm vs 11.5 ± 3.8 mm, p < 0.05; 6.8 ± 2.1 mm/m(2) vs 6.6 ± 2.4 mm/m(2); 0.17 ± 0.06 mm/kg vs 0.17 ± 0.06 mm/kg, both p > 0.05). Applying BSA- and weight-indexed cut-off values decreased HCM diagnoses in the study group (48% vs 42%; 48% vs 39%, both p < 0.05), reclassified subjects in the largest, lightest and heaviest tertiles (≥2.03 m(2): 58% vs 45%; ≤70 kg: 37% vs 46%; ≥85 kg: 53% vs 25%, all p < 0.05) and improved predictive accuracy (AUC 0.76 [95% CI 0.69–0.82] vs 0.78 [0.72–0.85]; and vs 0.80 [0.74–0.87]; both p < 0.05). CONCLUSIONS: In genotype-positive subjects referred for family screening, differences in MWT across gender are mitigated after indexation by BSA or weight. Indexation decreases the prevalence of HCM, particularly in larger men, and improves the predictive accuracy for HCM-related events.